daje naj
proszę o szybką odpowiedź ​


Daje Naj Proszę O Szybką Odpowiedź class=

Odpowiedź :

1)

[tex](2x - 3)(4x - 3) - (2x - 3)(3x - 1) = 8 {x}^{2} - 6x - 12x + 9 - (6 {x}^{2} - 2x - 9x + 3) = 8 {x}^{2} - 18x + 9 - 6 {x}^{2} + 2x + 9x - 3 = 2 {x}^{2} - 7x + 6[/tex]

2)

[tex](2a - 3)(3x - 1) = 6ax - 2a - 9x + 3[/tex]

3)

[tex] - (3 + 2a)( {a}^{2} - 3) = - (3 {a}^{2} - 9 + 2 {a}^{3} - 6a) = - 3 {a}^{2} + 9 - 2 {a}^{3} + 6a[/tex]

4)

a)

[tex]2(3m - 12) - (7 - 2n + 3m) - ( - 3m + 2n - 4) = 6m - 24 - 7 + 2n - 3m + 3m - 2n + 4 = 6m - 27[/tex]

b)

[tex] - 3m + 2n - 4 - 2(7 - 2n + 3m) = - 3m + 2n - 4 - 14 + 4n - 6m = - 9m + 6n - 18[/tex]